1989
DOI: 10.1007/bf00273522
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of liposome encapsulation on the vesicant properties, acute and cardiac toxicities, and antitumor efficacy of doxorubicin

Abstract: Numerous studies have demonstrated that liposomal encapsulation decreases the life-threatening chronic and acute toxicities of doxorubicin in the face of unaltered or improved antitumor activity. Minimal attention has been paid to the encapsulation effect on the lesser toxicities of the drug, specifically the vesicant properties. In this report we assess the effect of the encapsulation of doxorubicin in an egg-yolk phosphatidylcholine (EPC) cholesterol liposome on the drug's topical toxicity. In addition, to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…by guest www.bloodjournal.org From (5 mg/kg DOX). The free DOX dose (3 mg/kg) was chosen to correspond to a value below (at approximately 10% of) its previously reported LD 50 value 47 of approximately 26 mg/kg. The L-DOX or f-L-DOX dose (5 mg/kg) used was equitoxic to 3 mg/kg free DOX, based on previous findings showing that the LD 50 of L-DOX was between 1.5 and 2 times higher than that of free DOX in mice.…”
Section: Therapeutic Efficacy Of F-l-dox In Murine Leukemia Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…by guest www.bloodjournal.org From (5 mg/kg DOX). The free DOX dose (3 mg/kg) was chosen to correspond to a value below (at approximately 10% of) its previously reported LD 50 value 47 of approximately 26 mg/kg. The L-DOX or f-L-DOX dose (5 mg/kg) used was equitoxic to 3 mg/kg free DOX, based on previous findings showing that the LD 50 of L-DOX was between 1.5 and 2 times higher than that of free DOX in mice.…”
Section: Therapeutic Efficacy Of F-l-dox In Murine Leukemia Modelsmentioning
confidence: 99%
“…The L-DOX or f-L-DOX dose (5 mg/kg) used was equitoxic to 3 mg/kg free DOX, based on previous findings showing that the LD 50 of L-DOX was between 1.5 and 2 times higher than that of free DOX in mice. 47,48 Median survival time for the 4 groups of mice were 25.5, 28.5, 35, and more than 80 days, respectively (Figure 4). The data clearly indicated that L-DOX was more effective than free DOX in prolonging animal survival (P ϭ .0159; log-rank test), presumably because of the prolonged systemic circulation time of L-DOX compared to free DOX.…”
mentioning
confidence: 99%
“…Despite the development of a number of new antifungal agents (10), amphotericin B (AmB) formulated as a micelle suspension with deoxycholate (Doc-AmB) remains one of the most effective agents in the treatment of systemic fungal infections (18). However, Doc-AmB use is often limited by the development of kidney toxicity manifested by renal vasoconstriction with a significant decrease in the glomerular filtration rate and renal plasma flow and by renal potassium and magnesium wasting (10,18,39).Incorporation of many drugs, including chemotherapeutic and antifungal agents, into liposomes minimizes toxicity without a loss of the pharmacological effect (2,15,22,29). In addition, when AmB was complexed with lipid to form AmB lipid complex (ABLC), AmB was selectively taken up by mononuclear phagocytes and delivered principally to the liver and the lung (16,28).…”
mentioning
confidence: 99%
“…Incorporation of many drugs, including chemotherapeutic and antifungal agents, into liposomes minimizes toxicity without a loss of the pharmacological effect (2,15,22,29). In addition, when AmB was complexed with lipid to form AmB lipid complex (ABLC), AmB was selectively taken up by mononuclear phagocytes and delivered principally to the liver and the lung (16,28).…”
mentioning
confidence: 99%
“…[3][4][5] For example, liposomes are widely used to improve the delivery of many anticancer, antibiotic and antifungal drugs, such as doxorubicin, epirubicin, vincristine and ciprofloxacin. [6][7][8][9][10] The effectiveness of this formulation approach is dependent on the rate of drug release from the liposomes.…”
mentioning
confidence: 99%